The Effect of Tourism Revenue on Community Welfare through Economic Growth - Sabaty Prestiantika; Sishadiyati Sishadiyati (PT. Anagata Sembagi Education, 2024)
This study aims to determine the direct influence of tourism income on the well-being of the population and the indirect impact of tourism income on public welfare through economic growth. The research utilizes secondary data sourced from the Central Statistical Authority of Surabaya and the Regional Revenue Authority of Surabaya, Indonesia, covering the years 2013 to 2022. The methodological approach adopted for this study is linear regression, incorporating intervening variables to assess these relationships. The analysis reveals that tourism income has a significant positive impact on the well-being of the population when considered directly. This direct influence is substantial, indicating that higher tourism revenue correlates strongly with improved living standards for the people of Surabaya. Additionally, when examining the indirect effects, the study finds that tourism income also positively impacts public welfare through the channel of economic growth. However, this indirect impact, while significant, is of lower magnitude compared to the direct influence. Overall, the findings suggest that promoting tourism can be a robust strategy for enhancing the well-being of the population in Surabaya. The dual pathways—directly through income and indirectly via economic growth—highlight the multifaceted benefits of a thriving tourism sector for public welfare.